Merumuskan Ulang Konsep Moralitas: Sumbangan Pemikir Feminis - Paulus Bagus Sugiyono (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2020)
The aim of this article is to re-conceptualize the meaning of morality according to the perspective of feminists.This article employed the method of literature review within the qualitative approach. Morality, in the historyof western thought, is often related with the concept offered by Immanuel Kant. Human being is perceived tohave a sufficient rationality to access the universal morality. Therefore, there is no reason for not following theprinciples of morality. The use of rationality definitely denies all of the contingent things, such as feeling,sensitivity, and inclination. The result of this study shows that the feminists tried to reflect on these contingentthings, so that they could re-conceptualize the meaning of morality. They did believe that these contingentthings have given such an influential meaning for the concept of morality. Besides, this study also points outthat the concept of care ethics is thus a fruit of the feminists’ thought. Even though, care ethics would notdefinitely substitute Kantian ethics, but rather complement it, so that the paradigm of the morality can be seenbroader from several perspectives. This entwined paradigm, between Kantian and care ethics, is then can beemployed to analyze various social phenomena that occur in our society.